Code-Switching, Embodiment and Object Status in Heritage Environments: Demonstrating a Neolithic Quern During a Guided Tour - Wilton, Antje (Social Interaction. Video-Based Studies of Human Sociality, 2023)
The paper presents an analysis of a demonstration of a Neolithic quern in which code-switching and embodied actions are employed to interactionally construct the status of the object and the reference to both past and present realities. The data show how participants of a guided tour engage with these realities by treating the quern as accessory, exhibit and prop to connect experiences in the present with the realities of life in the Neolithic past. The demonstration as part of the guided tour does not merely provide a simulation of the past, but also an approximation of it through verbal and bodily means.